University of Costa Rica’s english diagnostic test 2022: evidence of validity and reliability - Araya Garita, Walter (2024)
Abstract: The English Diagnostic Test aims to assess reading comprehension skills for first year students at the University of Costa Rica. In 2022, this test consisted of four instruments with 55 items. Instruments were based on an academic reading, following the criteria B2+ or C1 level according to Common European Framework of Reference for languages. This paper explores the evidence of validity and reliability from 1732 first-year students virtually assessed in March of 2022, using the platform of the Programa de Evaluacion en Lenguas Extranjeras (PELEx). Results from this study demonstrated the unidimensionality of the four instruments. Cronbach’s alphas for the four instruments anged from 0.79 to 0.84. Evidence collected in this study supports the work done by the School on Modern Languages in the development of valid and reliable instruments for the English Diagnostic Test, as part of the current needs of new students for undergraduate programs at the University of Costa Rica. Keywords: reading comprehension, assessment, validity, reliability